2011
DOI: 10.1039/c1cc11940k
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous polymeric sensors based on temperature-induced polymer phase transitions and solvatochromic dyes

Abstract: This feature article provides, for the first time, an overview of the research that guided the way from fundamental studies of the thermo-responsive phase separation of aqueous polymer solutions to polymeric sensor systems. The incorporation of solvatochromic dyes into thermoresponsive polymers as well as the concepts of polymeric sensors are presented and discussed in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
132
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(132 citation statements)
references
References 155 publications
0
132
0
Order By: Relevance
“…26 Early works on scanning microscopy-based thermometry employing diagnostic techniques 24,59,60 and either electrical or scanning probe microscopy (with a particular emphasis on microelectronics and data storage devices) 25 were available between 1999 and 2005. Three other reviews partially covering the subject and dealing with ceramic phosphors that can withstand extreme temperatures, 61 multiple optical chemical sensors 62 and temperature-stimuli polymers 63 have been published in 2011.…”
Section: +mentioning
confidence: 99%
See 2 more Smart Citations
“…26 Early works on scanning microscopy-based thermometry employing diagnostic techniques 24,59,60 and either electrical or scanning probe microscopy (with a particular emphasis on microelectronics and data storage devices) 25 were available between 1999 and 2005. Three other reviews partially covering the subject and dealing with ceramic phosphors that can withstand extreme temperatures, 61 multiple optical chemical sensors 62 and temperature-stimuli polymers 63 have been published in 2011.…”
Section: +mentioning
confidence: 99%
“…63 An example is the use of PS and polyacylonitrile to increase the solubility of C 70 , avoiding simultaneously the luminescence crosstalk with oxygen.…”
Section: Polymer Based Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is part of a larger research field, namely functionalized polymers. [13][14][15][16] It has been shown that pH…”
Section: Introductionmentioning
confidence: 99%
“…These stimuli-responsive polymers are prepared by combination of a responsive polymer phase transition (coil-to-globule) with a solvatochromic dye. [38] It is known that poly(N-isopropylacrylamide) (PNIPAM) is one of the most important water-soluble polymers, which exhibits a heat-induced phase transition from coiled to globular state in an aqueous solution in response to temperature changes across a lower critical solution temperature (LCST) at 32°C, [39] by expanded conformation in water below the LCST due to strong hydration, and changes to compact forms above the LCST by dehydration. [40,41] Continuing our works on heterocyclic chemistry, [42][43][44][45] herein, we wish to report a new heterocyclic pH-responsive dye based on diazenylphenyl-1,3,4-oxadiazol moiety and its use in a novel water-soluble polymeric sensor, which responds to both pH and temperature.…”
Section: Introductionmentioning
confidence: 99%